Postoperative respiratory complications and disposition in patients with type 1 laryngeal clefts undergoing injection or repair – A single institution experience. (April 2020) - Harris, Vandra C.; Dalesio, Nicholas M.; Clark, James; Nellis, Jason C.; Tunkel, David E.; Lee, Andrew H.; Skinner, Margaret
Abstract: Objective: Identify incidence and factors associated with respiratory complications after type 1 cleft repair. Methods: Retrospective chart review of patients who underwent cleft repair over a 5-year period performed by a single surgeon. Primary endpoint was respiratory complications (oxygen desaturation <90%). Fisher's exact test was used to identify differences between repair types (endoscopic carbon dioxide laser-assisted repair and injection laryngoplasty). Logistic regression was used to identify predictors of respiratory events. Results: Fifty-five patients were included. Thirty-four (62%) patients underwent endoscopic carbon dioxide laser-assisted repair and 21 (38%) underwent injection laryngoplasty. Average hospital stay for each group was 1.6 days (SD = 3.1) and 0.6 days (SD = 0.9), respectively. Desaturations occurred in three patients (9%) in the laser-assisted repair group and one patient (4%) in the injection group. All occurred within 3 h after surgery and resolved with supplemental oxygen, oral airway placement, and/or mask ventilation. Two affected patients had comorbid diagnosis of asthma (one had poor medication compliance), and one had a history of developmental delay and hypotonia. In the injection group, desaturations occurred in one patient with a history of tracheal stenosis and double aortic arch. No correlation existed between repair type and desaturation ( p  = 0.57). No variables were significant predictors of events. Conclusions: In this cohort, respiratory events after type 1 laryngeal cleft repair occurred early in the postoperative period, in children with cardiac and pulmonary comorbidities. This suggests postoperative admission may only be necessary for a select group of patients undergoing type 1 cleft repair. However, further research is needed to determine criteria for same-day discharge.